Building Resilience to Climate Change in South Caucasus Agriculture - Ahouissoussi, Nicolas (Washington, DC: World Bank, 2014)
This book illustrates the World Bank’s commitment to assist countries to respond to the opportunities and challenges posed by climate change. Undertaken in collaborative partnership with policy makers, farmers, civil society, and other stakeholders in Armenia, Azerbaijan and Georgia, it provides a much needed response to the call for action by quantifying the impact and identifying key priorities for policies, programs, and investments to reduce the vulnerability of agricultural systems to climate change in the South Caucasus.